2012
DOI: 10.1038/sc.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the glomerular filtration rate using serum cystatin C levels in patients with spinal cord injuries

Abstract: In patients with SCI, GFR can be estimated independent of age, sex and muscle mass by a newly developed equation based on a single serum CysC value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…10,11,18 It is produced by most nucleated cells at a stable rate and is, most importantly, not affected by the level of muscle mass, gender or age, 10 which makes it a promising test in this patient population and hence it should probably substitute p-creatinine in the future. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,18 It is produced by most nucleated cells at a stable rate and is, most importantly, not affected by the level of muscle mass, gender or age, 10 which makes it a promising test in this patient population and hence it should probably substitute p-creatinine in the future. …”
Section: Discussionmentioning
confidence: 99%
“…Only three of the papers used the gold standards 51 Cr-EDTA clearance 10,11 or 99m Tc-DTPA clearance. 2 They all concluded that s-creatinine underestimated the renal deterioration, except for one study, Sepahpanah et al, 17 which concluded that s-creatinine was better in monitoring renal function than creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that serum CysC levels could detect the early decrease of renal function and correlated better with 50 Cr EDTA clearance than sCr in the general population . Although only a few studies have tested the usefulness of CysC as a surrogate marker of renal function in the NB population, the authors showed that CysC is more correlated with 51 Cr‐EDTA‐clearance or inulin clearance than sCr or sCr‐based eGFR . Recently, Mingat et al reported that the CysC‐based eGFR by CKD‐EPI equation was the most precise method in NB patients with various neurologic disorders, whether ambulatory or wheelchair …”
mentioning
confidence: 99%
“…The panel recommends a cystatin C test for early detection of renal impairment, because cystatin C is less affected by muscle mass than creatinine ( LoE 5, GoR C1 ) …”
Section: Summary Of the Guidelinesmentioning
confidence: 99%